2013
DOI: 10.1155/2013/396091
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Different Surface Configurations on Stability of Miniscrews

Abstract: Introduction. The aim of this study was to analyze the effects of screw design and force application on the stability of miniscrews, using RTT, SEM, and histomorphometric analyses. Materials and Methods. Eighty cylindrical, self-drilling, and Ti6Al4V alloy miniscrews (1,6 × 6 mm) were used. Four mini-screws were inserted in fibulas of each rabbit, and 115 G of force was immediately applied. Four miniscrews were inserted in the other fibula, on which no force was applied. Eight weeks after insertion, osseointeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…It was thought that length of the mini screw could be the cause of the fracture, but as the most commonly used length of the mini screws is 8 mm in orthodontic practice, it was decided to change the experimental bone to the fibula, rather than changing the dimension of the mini screw. 27 It has been reported that the most suitable wavelength for biostimulation is 550-950 nm. 28 The laser types in this range are He-Ne and diode laser systems.…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that length of the mini screw could be the cause of the fracture, but as the most commonly used length of the mini screws is 8 mm in orthodontic practice, it was decided to change the experimental bone to the fibula, rather than changing the dimension of the mini screw. 27 It has been reported that the most suitable wavelength for biostimulation is 550-950 nm. 28 The laser types in this range are He-Ne and diode laser systems.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore the thickness of dense cortical bone has been suggested as a critical factor affecting the primary stability of miniscrews, (Deguchi et al 2011) and larger diameter miniscrews have showed a higher removal torque than smaller ones, (Wilmes et al 2006;Topcuoglu et al 2013) which means better stability. However, there is a limitation to improving stability by increasing the diameter of miniscrews because they should be small enough to be placed into the narrow area between the roots of the teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Implant stability is defined as the capacity of the implant to withstand loading in axial, lateral, and rotational directions [4]. Primary stability is mainly dependent on the mechanical characteristics of the original bone like its local quality and quantity, the type of implant used including its geometry, diameter, length & surface characteristics, and the surgical techniques employed [5,6].Secondary implant stability represents enhancement of the stability as a result of peri-implant bone formation through gradual bone remodeling and osteoconduction, with the possibility of new bone formation at the implant-bone interface and influenced by the implant surface characteristics [7,8]. Contemporary knowledge indicates that the degree of micromotion at the bone-implant interface during initial healing is of utmost importance in achieving good secondary stability [9][10][11].…”
mentioning
confidence: 99%